Annual gametogenic phenology of oyster, Magallana bilineata (Röding, 1798) collected from the west coast of Moheshkhali Island, Cox's Bazar, Bangladesh - Md. Jasim Uddin; Md. Shamsur Rahman; Saima Sultana Sonia; Sheikh Khadijatul Kubra; Md. Sujon Mia; Selina Yeasmine (Heliyon, 2024)
The current study aimed to describe the annual gametogenic phenology of the oyster Magallana bilineata (Röding, 1798) (=Crassostrea madrasensis), which is found on the west coast of Moheshkhali Island, Cox's Bazar, Bangladesh. Samples were drawn monthly from the intertidal region during low tide, from which 20 adult individuals were selected at random for biometry and histology. The mean condition index (CI), a ratio of tissue wet weight (g) to shell length (cm), varied from 0.58 ± 0.08 to 1.32 ± 0.36. Histology revealed two spawning cycles in the habitat of M. bilineata over the 12 months of the study. Gametogenesis initiated in December and May, and ripe animals principally occurred from July to September and February to May. In the habitat, M. bilineata exhibited two spawning peak periods: April to June and August to October. The undifferentiated stage as a preparatory step for the next spawning extended from November to February for the first spawning cycle and for a brief period in June for the next spawning cycle. The initiation of spawning in March could be associated with the high-level decline of salinity and increased temperature between February and March, in association with the annual rainfall start, whereas the next spawning cycle could be associated with a gradual increase in salinity. No spawning activity was reported from December to February, when the water temperature remained below 22 °C. Further study could be undertaken on the timing of spatfall of M. bilineata in the habitat to harvest spats for commercial farming of this promising species.